Pengaruh Disiplin Kerja dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT. Darma Henwa Asam-Asam Coal Project (ACP) Kabupaten Tanah Laut - Jamidah Jamidah; Syahrani Syahrani; Fanlia Adiprimadana Sanjaya (Jurnal Manajemen Bisnis Era Digital, 2024)
This research aims to (1). To find out whether work discipline has a significant effect on the performance of PT employees. Darma Henwa (ACP) Tanah Laut Regency. (2). To find out whether leadership style has a significant effect on the performance of PT employees. Darma Henwa (ACP) Tanah Laut Regency. (3). To find out whether discipline and leadership style simultaneously have a significant effect on the performance of PT employees. Darma Henwa (ACP) Tanah Laut Regency. The method in this research uses quantitative methods and data analysis techniques use multiple linear regression. The sample for this research consisted of 74 employees in the PT operator sector. Darma Henwa (ACP) Tanah Laut Regency and the data collection techniques used in this research were direct observation and distribution of questionnaires at PT. Darma Henwa (ACP) Tanah Laut Regency.The research results show that work discipline has a significant effect on the performance of PT. Darma Henwa (ACP) Tanah Laut Regency, as well as leadership style have a significant influence on the performance of PT. Darma Henwa (ACP) Tanah Laut Regency. Discipline and leadership style greatly influence employee performance at PT. Darma Henwa Asam-Asam Coal Project (ACP). Good discipline and effective leadership are proven to increase efficiency, productivity and job satisfaction. These two factors explain 59.4% of the variation in employee performance, indicating the importance of discipline and leadership in improving performance.